2020
DOI: 10.1016/j.jhazmat.2019.121891
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens in municipal wastewater and receiving waters in the Beijing-Tianjin-Hebei region, China: Occurrence and risk assessment of mixtures

Abstract: The potentially high release of estrogens to surface waters as a result of high population density and local livestock production in the Beijing-Tianjin-Hebei region may pose adverse effects on the reproductive systems of aquatic organisms. This study found that total measured concentrations of estrone (E1), 17β-estradiol (E2), estriol (E3), 17αethinylestradiol (EE2) and diethylstilbestrol (DES) were 468±27.2 ng/L in treated wastewater and 219±23 ng/L in river waters in this region. E2, E3 and EE2 were the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(10 citation statements)
references
References 60 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…For example, Yao et al detected a high concentration of EDCs with a range of 0.85–2619 ng g −1 ww in wild fishes from two major rivers in China; 45 Kei et al also found a high concentration of EE2 in receiving river of swine-raising facilities. 46 BP-3 and EE2 as an indicator of contaminant loading should be included in future water monitoring programs to provide information support for the formulation of relevant regulations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yao et al detected a high concentration of EDCs with a range of 0.85–2619 ng g −1 ww in wild fishes from two major rivers in China; 45 Kei et al also found a high concentration of EE2 in receiving river of swine-raising facilities. 46 BP-3 and EE2 as an indicator of contaminant loading should be included in future water monitoring programs to provide information support for the formulation of relevant regulations.…”
Section: Resultsmentioning
confidence: 99%
“…It appears from the discussion presented above that the most efficient way to mitigate natural estrogens is to enhance their removal in municipal WWTPs. , In addition, it should be noted that the concentration of total natural estrogens of S24 was found to be as high as 36.6 ng/L, while this high concentration was unlikely to be caused by the discharge of municipal WWTP effluent. In fact, S24 was the farthest downstream sampling site, and there was no municipal WWTP near this site, implying the other inputs of natural estrogens, likely due to pollution diffusion or discharge of the untreated municipal wastewater. …”
Section: Resultsmentioning
confidence: 99%
“…62 Moreover, the maximum permissible standard of 7000 pg mL −1 for 4-NP in ocean water was confirmed by the USPEA to ensure the normal growth of most marine animals. 64 Lei et al 65 investigated several estrogens (i.e., E1, E2, E3, EE2, and DES) in water samples from the Beijing-Tianjin-Hebei region, of which the total concentration in wastewater was 0.468 ± 0.0272 ng mL −1 and was 0.219 ± 0.023 ng mL −1 in river water. Natural or synthetic estrogens have negative effects on surface waters, particularly for fish species.…”
Section: Contamination Events Official Warnings and Safety Guidelinesmentioning
confidence: 99%